Super genes : unlock the astonishing power of your DNA for optimum health and well-being - Chopra, Deepak; Tanzi, Rudolph E. (Harmony, 2015)
"The authors of the New York Times bestseller Super Brain present a bold new understanding of our genes and how simple changes in lifestyle can boost genetic activity. The leap into "radical well-being" is a promise waiting to be fulfilled. "You are not simply the sum total of the genes you were born with," writes Deepak Chopra and Rudy Tanzi. "You are the user and controller of your genes, the author of your biological story. No prospect in self-care is more exciting." Learning how to shape your gene activity is at the heart of this exciting and eagerly-anticipated book from the bestselling duo behind Super Brain, which became a nationwide hit on public television. For decades medical science has believed that genes determined our biological destiny. Now the new genetics has changed that assumption forever. You will always have the genes you were born with, but genes are dynamic, responding to everything we think, say, and do. Suddenly they've become our strongest allies for personal transformation. When you make lifestyle choices that optimize how your genes behave, you can reach for a state of health and fulfillment undreamed of even a decade ago. The impact on prevention, immunity, diet, aging, and chronic disorders is unparalleled"--